Fantasies of Immediacy, or, the Boundaries of the Book in Eighteenth Century Travel Narratives - Buschmeier, Matthias (Romanticism and Victorianism on the Net, 2010)
This article explores a structural shift in techniques of representation in eighteenth-century travel literature as a reaction to the changing needs of cameralist governance, one in which space is no longer grasped as enyclopedic and all-encompassing. Instead of being understood as static territory, space is increasingly represented as a dynamic and continually updatable dataset. As a consequence, travel literature itself goes in search of new representational modes appropriate to this new understanding of space. And as I show, the medium of the book becomes increasingly problematic in this regard. As early modern travel literature (ars Apodemica) largely splits in the eighteenth century into statistics and geography on the one hand and literary travel experiences on the other, each of these categories requires new forms of mediation for their successful presentation. Common to both, however, remains a desire to communicate an immediacy of perception through representation. Taking Friedrich Nicolai’s Beschreibung einer Reise durch Deutschland und die Schweiz im Jahre 1781 as my primary example, I show how the medium of the book arrives at its own media boundary, one whose transgression necessarily results in failure because it can no longer account for an epistemological divide that has already transpired. This difference has far-reaching implications for the place of the book within the humanistic sciences today.